EDUCATION OF PRIMARY CLASS STUDENTS IN THE SPIRIT OF NATIONAL AND GENERAL HUMAN VALUESTECHNOLOGY - Jorabek Jovliev (International Journal of Innovations in Engineering Research and Technology, 2023)
It is shown that the role of national and universal values in the education of young people is invaluable. The importance of educating young people through national values in the educational process is emphasized.